Safeguardability evaluation for a conceptual tritium production facility - Kim, Jiyoung; Kim, Yeongchan; Kang, Changwoo; Ko, Danwoo; Kim, Hyolee; Woo, Seung Min (Nuclear engineering and technology, 2025)
Tritium is an isotope essential for nuclear fusion reactor operations. Since it can be used for manufacturing nuclear weapons, nuclear safeguards are required for its peaceful use. This study analyzed and discussed the safeguarding of conceptual tritium production facility. Tritium production capacity of pressurized water reactor was analyzed using MCNP6.2 code. Tritium was assumed to be produced using tritium-producing burnable absorber rods (TPBARs). The 17 X17 nuclear fuel assembly with various loading configurations of TPBARs was designed and simulated as a function of the burnup. Therefore, a formula for analyzing the total tritium produced as a function of burnup and lithium-6 enrichment was developed using a regression methodology. Within the evaluated area, the error of this formula was less than 6.46 %. A conceptual material balance area for a tritium extraction facility (TEF) was assumed. Through literature review, the cases (1, 5, 10 g) of the equivalent-significant quantity (SQ) of tritium were classified, and TEF σMUF was calculated according to the IAEA's suggestion (3σMUF < SQ). As a result, the σMUF of TEF was calculated to be within 4–22 g of the equivalent-SQ (1–10 g). Therefore, the number of TPBARs that can be processed per cycle in the TEF was 4–228, depending on the equivalent-SQ value. Thus, the applicability of TEF's safeguards was discussed.